Juridical Analysis Of The People's Final Step To Seek Justice By Way Of Viral On The Media In The Perspective Of Legal Politics - Prasetyo, Yogi; Febriansyah, Ferry Irawan; Firdausi, Ulya Shafa (Universitas Islam kadiri, 2025)
The development of the current era requires humans to use various technologies, one of which is the internet. With social media or the internet, humans have a very important role in resolving various injustices in legal practice in this country. Because efforts to achieve justice cannot be ignored. A rule of law cannot be ignored. may be apathetic towards the struggle and every effort to uphold justice. the concept of justice is very important so that a rule of law becomes the basis for all parties, both citizens and leaders as certainty in resolving various legal problems they face. so many use social media in solving various cases of injustice what the media can reveal tends to be resolved openly and can be followed and controlled by the public. Today's media is a place for citizens to seek and realize justice in accordance with their role. This mass media also monitors law enforcement and justice in the country. this is it. the role of netizens is a very large mass in raising a case so that it goes viral it is very important without a response from netizens then a case will not go viral. The reason someone uploads to social media for the first time is because there are so many social media users and there are almost all over the world , secondly, because social media is an internet-based technology where news dissemination will be faster than word of mouth, thirdly, if it is viral in the mass media, related parties will handle it quickly. And this is what politics does law in dealing with legal cases that do not get justice before they are viral in the mass media, legal politics also influences the strength or weakness or how important the legal objectives are to be achieved.